VARIATION OF INDOOR RADON CONCENTRATION WITHIN A RESIDENTIAL COMPLEX. Issue 3 (15th April 2020) - Sferle, Teofana; Dobrei, Gabriel; Dicu, Tiberius; Burghele, Bety-Denissa; Brişan, Nicoleta; Cucoş (Dinu), Alexandra; Catalina, Tiberiu; Istrate, Andrei; Lupulescu, Alexandru; Moldovan, Mircea; Niţă, Dan; Papp, Botond; et al.
Abstract: A recent challenge in research dedicated to residential exposure to radon comes from the growing number of houses retrofitted to reduce energy consumption. Efficiently insulated buildings and modern architectural solutions can lead to the accumulation of high levels of indoor pollutants. A systematic analysis was conducted in a residential complex (consisting of six houses) in order to assess the annual radon concentration and to evaluate the intensity of the relationships with various factors, such as the indoor-outdoor temperature differences, wind speed and wind direction. Three types of occupational behaviour, influencing the ventilation rate of the dwellings and, implicitly, the indoor radon activity concentration were observed. By calculating the partial correlation coefficient between the radon concentration and the wind direction, with the wind speed as the control variable, for all six houses the correlation coefficient presents negative values.